Preventing spread of SARS-CoV-2 and preparing for the COVID-19 outbreak in the surgical department: perspectives from two Scandinavian countries. Issue 5 (6th May 2020) - Lindeman, Robbert-Jan; Sund, Malin; Löfgren, Jenny; Basso, Trude; Søreide, Kjetil
ABSTRACT: A COVID-19 pandemic was declared on March 11 by the World Health Organization (WHO). The first cases of COVID-19 were confirmed on January 31 in Sweden and on February 26 in Norway. Despite being similar countries with universal healthcare systems, the governmental approaches to mitigation of the epidemic have varied considerably. Norway initiated a societal lockdown effective from March 12, the same day as the first confirmed death. Sweden has initiated a more laxed and gradual strategy based on the appeal for a strong personal sense of responsibility to mitigate the viral spread. In both countries, the first weeks of preparation has seen a strong reduction in elective surgery, with several implemented principles to mitigate SARS-CoV-2 spread and prepare for surgical care for COVID-19 diseases as needed. This invited leading article gives a brief overview of some of the early experiences of the outbreak in two Scandinavian countries.